Kontradiksi Pengobatan Tradisional Dan Medis: Studi Kualitatif Penggunaan Jagung (Zea Mays) Topikal Dalam Penanganan Cacar Air - Kalsum, Santika Umi; Wijaya, Nadina; Septiansya, Elgia Ardia; Sucipto, Ade; Laksono, Eko Budi; Rahayu, Sri; Supriyatna, Yayat (STIKES Borneo Cendekia Medika, 2025)
The use of natural ingredients in traditional medicine practices is still commonly found in various regions of Indonesia. One such practice is the topical application of corn (Zea mays) to treat chickenpox. This study aimed to explore the practice and public as well as health professionals’ perceptions toward this treatment. The research was conducted in Arut Selatan District, Kotawaringin Barat Regency, Central Kalimantan, using a qualitative descriptive case study approach. A total of 48 respondents participated in this study, consisting of 43 community members (users and family) and 5 health workers. Data were collected through face-to-face and online interviews and analyzed thematically. The findings indicate that the practice continues due to beliefs in its ability to accelerate healing, reduce itching and heat, and is rooted in generational experience. Symbolic beliefs, such as the notion that corn must be “stolen” to be effective, were also reported. Meanwhile, health workers expressed varying perspectives—from being unaware of the practice to expressing concern about infection risks if applied without medical supervision. This study highlights the need for culturally sensitive educational approaches that integrate local traditional values with modern medical safety principles, promoting holistic and contextual healthcare practices.